Body dysmorphic disorder: a treatment manual - Veale, David; Neziroglu, Fugen A (Wiley-Blackwell, 2010)
This book is a unique treatment manual which looks at the assessment of BDD, offering an treatment model in the form of CBT and pharmacotherapy Summarises the current knowledge and theoretical perspectives about BDD Covers the practical aspects of assessment, engagement, and therapy Uses a number of practical resources, including client handouts.